The psychosocial impact of cancer diagnosis in pregnancy: a multicenter cohort study of psychosocial challenges in pregnant cancer patients and their partners - Huis in 't Veld, Evangeline A.; van Gerwen, Mathilde; van Dijk-Lokkart, Elisabeth M.; Vandenbroucke, Tineke; Dandis, Rana; LeJeune, Charlotte L.; van Assche, Indra; Cardonick, Elyce; Peters, Inge T. A.; Fagotti, Anna; Lok, Christianne; Boere, Ingrid; et al. (Frontiers in Psychology, 2026)
ObjectiveCancer during pregnancy poses significant physical and psychological challenges for expectant mothers and their partners. While elevated stress and anxiety levels in pregnancy are well-documented, the specific parental psychological impact of cancer during pregnancy remains unexplored, and could be different for patients and partners. This study represents the first full prospective analysis, complementing earlier retrospective research by analyzing self-reported perspectives and coping strategies among both pregnant cancer patients and their partners.MethodsParticipants were prospectively recruited within the International Network on Cancer, Infertility, and Pregnancy (INCIP) across The Netherlands, Belgium, USA and Italy. Participants completed the Cancer and Pregnancy Questionnaire (CPQ), developed by our research team, and a shortened version of the Cognitive Emotion Regulation Questionnaire (CERQ). Differences in concerns and coping strategies were analyzed using Wilcoxon Signed-Rank tests, Cliff's Delta for effect sizes, and Spearman's correlation analysis.ResultsBetween 2009 and 2024, 220 patients and 189 partners participated. Compared to partners, patients reported significantly greater concerns about their child's health and the implications of the disease, treatment, and upcoming delivery. Patients exhibited higher use of both adaptive (e.g., Positive Reappraisal, Refocusing) and maladaptive (e.g., Self-blame, Rumination) coping strategies, and a stronger desire to continue the pregnancy. Satisfaction with medical care was similar between groups. Maternal age at diagnosis was linked to maladaptive strategies (Catastrophizing and Blaming Others), while higher gestational age at diagnosis was associated with both adaptive (Positive Refocusing and Positive Reappraisal), and the maladaptive coping strategy Catastrophizing.ConclusionsThis study provides valuable insights into the psychological challenges experienced by pregnant cancer patients and their partners, emphasizing the need for personalized care that includes psychological support from the start.